TINJAUAN PARAMETER EKONOMIS KERAMBA BETON BLU UNIVERSITAS PATTIMURA AMBON - Lessil, Jaqueline Carolina; Hetharia, Wolter R; Buyang, Christy G (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
As a Public Service Agency, Pattimura University utilizes the potential of aquatic resources in the Inner Ambon Bay by using reinforced concrete fish cages. The construction of the Concrete Cage by BLU Pattimura University has not yet been supported by a financial feasibility study that could affect the business or investment outcomes, making it uncertain whether the project can achieve the required revenue targets to generate profit. This study aims to contribute by ensuring that the concrete cage project has the potential to become a profitable long-term investment through a review of its economic parameters. This serves as a reference in determining whether a project is feasible or not. The methods used include Net Present Value (NPV), Benefit Cost Ratio (BCR), Payback Period (PP), and Sensitivity Analysis. Based on the results of the sensitivity analysis, Scenario I shows an NPV value of Rp55,420,888, a BCR of 1.469086167, and a PBP of 3 years, 5 months, and 12 days. Scenario II has an NPV value of Rp76,200,487, a BCR of 1.644966103, and a PBP of 3 years, 1 month, and 1 day. Scenario III shows an NPV value of Rp87,811,946, a BCR of 1.743246279, and a PBP of 2 years, 10 months, and 26 days. Scenario IV has an NPV value of Rp77,430,028, a BCR of 1.625740809, and a PBP of 3 years, 1 month, and 2 days. Among the four fish scenarios, the barramundi (Lates calcarifer) shows the highest profitability potential with a positive NPV of Rp87,811,946, a BCR ≥ 1 with a value of 1.743246279, and a PBP of 2 years, 10 months, and 26 days under Scenario III. Keywords: Concrete Cage, Financial Feasibility, Net Present Value, Benefit Cost Ratio, Payback Period, Sensitivity Analysis.